Integrating of Human Resource Development Innovation and Utilization of Information Technology on Performance - Istiqhotsah, Vyatriaka; Maklassa, Dg.; Muchran, Muchriady (Manunggal Halim Jaya, 2024)
This research aims to analyze and understand the influence of innovation in human resource development and the use of information technology on the performance of beauty clinic employees in Makassar City. The research design that will be used in this research is explanatory. The location of this research is the Alisa Skin Clinic in Makassar City. The population in this study was 89 employees at several beauty clinics in the city of Makassar. The sampling technique used in this research was saturated. The sample taken in the research was 82 respondents (based on total employees in several beauty clinics in Makassar City) at Alisa Skin Clinic, Anna Clinic Makassar, and Fraizthetic Clinic. The data analysis technique used in this research is multiple linear regression analysis with the help of software via the Statistical Product And Service Solution application to carry out calculations. Multiple linear regression analysis was used. The research results show that innovation in human resource development has a positive and significant effect on the performance of beauty clinic employees in Makassar City. The use of information technology has a positive but not significant effect on the performance of beauty clinic employees in Makassar City.